Optimization of sintering conditions for improved microstructural and mechanical properties of dense Ce0.8Gd0.2O2-δ-FeCo2O4 oxygen transport membranes. Issue 1 (January 2021) - Zeng, Fanlin; Malzbender, Jürgen; Baumann, Stefan; Nijmeijer, Arian; Winnubst, Louis; Ziegner, Mirko; Guillon, Olivier; Schwaiger, Ruth; Meulenberg, Wilhelm Albert
Abstract: Ce0.8 Gd0.2 O2- δ -FeCo2 O4 composite is an excellent oxygen transport membrane material with good chemical stability for applications in oxygen separation and membrane reactors. To improve microstructural and mechanical properties, sintering profiles for Ce0.8 Gd0.2 O2- δ -FeCo2 O4 composites were optimized. Different sintering temperatures are selected based on our study of phase interactions among the initial powder mixtures using high-temperature X-ray diffraction. The results reveal that the phase interaction at ∼1050 ℃ accelerates densification process, and a further increase of sintering temperature to 1200 ℃ contributes to the homogenization of the pore distribution. A higher density and an improved homogeneity of pore distribution result in enhanced mechanical strength. However, the density decreases once the sintering temperature reaches 1350 ℃. Hence, the optimal sintering temperature considering both microstructural and mechanical properties appears to be 1200 ℃. Sintering at this temperature results in a microstructure with a density exceeding 99 % with only small surface defects and a high average flexural strength of approximately 266 MPa.